A case report of human infection with avian influenza H10N3 with a complex respiratory disease history - Zhenxi Zhao; Siyi Luo; Yudong Gao; Min Dai; Jun Yan; Ying Yang; Hongwei Li; Yan Zhang; Zhipeng Mao (BMC Infectious Diseases, 2024)
Abstract Background On March 16th 2024, the first case of Human infection with avian influenza H10N3 since the end of the global COVID-19 Pandemic was reported in Kunming, China. To enhance comprehension of the source of infection and risk factors of the H10N3 virus infection, this case report summarizes the clinical features, epidemiological investigation, and laboratory test results. Provides recommendations for the prevention and control of Human infection with avian influenza H10N3. Case presentation A 51-year-old male with a history of COVID-19 infection and a smoking habit of 30 years, worked in livestock breeding and was exposed to sick and dead poultry before falling ill with fever and chills on 28th February 2024. A week later, he was diagnosed with severe pneumonia, influenza, and respiratory failure by the Third People's Hospital of Kunming(KM-TPH). He was discharged on 17th April and none of his 6 close contacts showed any symptoms of illness. Environmental samples taken from the epidemic spot revealed that peacock feces tested positive for avian influenza sub-type H9 and waterfowl specimens showed positive results for avian influenza sub-type H5. Gene sequencing conducted on positive specimens from the patient's respiratory tract by the Chinese Centre for Disease Control and Prevention (CCDC) showed a high degree of similarity (98.6–99.5%) with the strain responsible for the second global case of human infected with H10N3 (reported from Zhejiang, China 2022). Conclusions According to the available epidemiological information, there is limited evidence to suggest that H10N3 viruses are excessively lethal. However, adaptive site mutations have been observed in the H10N3 isoform of mammals. While it is unlikely that the H10N3 virus will spread among humans, the possibility of additional cases cannot be entirely ruled out. Symptoms of human infection with H10N3 avian influenza are similar to those of common respiratory infections, which may result in them being overlooked during initial clinical consultations. Therefore, it is essential to improve surveillance of the H10 sub-type of avian influenza and to increase the awareness of hospital-related workers of cases of pneumonia of unknown origin.